Impact of Concomitant Impairments of the Left and Right Ventricular Myocardial Strain on the Prognoses of Patients With ST-Elevation Myocardial Infarction - Lai, Wei; Jie, He; Jian-Xun, Dong; Ling-Cong, Kong; Jun-Tong, Zeng; Bo-Zhong, Shi; Dong-Ao-Lei, An; Bing-Hua, Chen; Song, Ding; Zheng, Li; Fan, Yang; Yi-Ning, Yang; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: The impact of concomitant impairments of left and right ventricular (LV and RV) strain on the long-term prognosis of acute ST-elevation myocardial infarction (STEMI) is not clear. Methods: We analyzed CMR images and followed up 420 first STEMI patients from the EARLY Assessment of MYOcardial Tissue Characteristics by CMR in STEMI (EARLY-MYO-CMR) registry (NCT03768453). These patients received timely primary percutaneous coronary intervention (PCI) within 12h and CMR examination within 1 week (median,5 days; range, 2-7 days) after infarction. Global longitudinal strain (GLS), global radial strain (GRS), and global circumferential strain (GCS) of both ventricles were measured based on CMR cine images. Conventional CMR indexes were also assessed. Primary clinical outcome was composite major adverse cardiac and cerebrovascular events (MACCEs) including cardiovascular death, re-infarction，re-hospitalization for heart failure and stroke. In addition, CMR data from 40 people without apparent heart disease were used as control group. Results: Compared to controls, both LV and RV strains were remarkably reduced in STEMI patients. During follow-up (median: 52 months, interquartile range: 29–68 months), 80 patients experienced major adverse cardiac and cerebrovascular events (MACCEs) including cardiovascular death, re-infarction, heart failure, and stroke. LV-GCS > -11.20% was an independent predictor of MACCEs (P < 0.001). RV-GRS was the only RV strain index that could effectively predict the risk of MACCEs (AUC=0.604, 95%CI [0.533, 0.674], P=0.004). Patient with RV-GRS ≤ 38.79% experienced more MACCEs than those with preserved RV-GRS (log rank P<0.001). Moreover, patients with the concomitant decrease of LV-GCS and RV-GRS were more likely to experience MACCEs than patients with decreased LV-GCS alone (log rank P = 0.010). RV-GRS was incremental to LV-GCS for the predictive power of MACCEs (continuous NRI: 0.327; 95% CI: 0.095 - 0.558; P = 0.006). Finally, tobacco use (P = 0.003), right coronary artery involvement (P = 0.002), and LV-GCS > -11.20% (P = 0.012) was correlated with lower RV-GRS. Conclusions: The concomitant decrease of LV and RV strain is associated with a worse long-term prognosis than impaired LV strain alone. Combination assessment of both LV and RV strain indexes could improve risk stratification of patients with STEMI.